Antisipasi Keterlambatan Proyek Pembangunan Shelter dengan Menggunakan Metode What-If Analysis - Ineu Widaningsih; Anastasia Lidya Maukar; Avania Shinta (President University, 2018)
The purpose of this study is to identify the delay in building shelter projects and activities that cause delays. This research will provide suggestions on steps to be taken to overcome delays. This research uses two methods of control, namely the